Landscape and Architecture Management of Thai Temples for Faith Fostering: Past to Present - โปษยะนันทน์, วสุ (Journal of Buddhist Studies Chulalongkorn University, 2017)
This article is adapted from the research “Landscape and Architecture Management of Thai Temples for Faith Fostering: Past to Present” which has resulted from the requirement to solve problems that Thai Buddhist temples are currently facing concerning the physical features and the decreasing of faith. The research results in principles and recommendations for management of landscape and architecture of Thai Temples to enhance faith, emphasizing on the awareness of the values of place of worship, respect of laws and regulations, active and effective control and implementation, systematic management planning in cooperation with multi-professional parties. These are, essentially and necessarily, based on good governance and participation for the highest benefi ts of the cultural heritage which belongs to all people.